2014
DOI: 10.3389/fpls.2014.00592
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrates in plant immunity and plant protection: roles and potential application as foliar sprays

Abstract: Increasing interest is devoted to carbohydrates for their roles in plant immunity. Some of them are elicitors of plant defenses whereas other ones act as signaling molecules in a manner similar to phytohormones. This review first describes the main classes of carbohydrates associated to plant immunity, their role and mode of action. More precisely, the state of the art about perception of “PAMP, MAMP, and DAMP (Pathogen-, Microbe-, Damage-Associated Molecular Patterns) type” oligosaccharides is presented and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
215
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(233 citation statements)
references
References 213 publications
2
215
1
1
Order By: Relevance
“…appeared to benefit more from the treatments with laminarin than those of the 'Alba' cv. Laminarin is a resistance inducer that can activate plant defense systems (Trouvelot et al, 2014). It was shown to reduce postharvest diseases of sweet cherry (Feliziani, Santini, Landi, & Romanazzi, 2013a), and to elicit defense responses in grapevine, where it can induce protection against B. cinerea and Plasmopara viticola (Aziz et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…appeared to benefit more from the treatments with laminarin than those of the 'Alba' cv. Laminarin is a resistance inducer that can activate plant defense systems (Trouvelot et al, 2014). It was shown to reduce postharvest diseases of sweet cherry (Feliziani, Santini, Landi, & Romanazzi, 2013a), and to elicit defense responses in grapevine, where it can induce protection against B. cinerea and Plasmopara viticola (Aziz et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1980s, crab and shrimp shell powder chitin and its deacetylation product chitosan have been used for crop farming as biopesticides, biofertilisers, and in seed coating formulation, and agricultural film (Ha and Huang 2007; El Hadrami et al 2010; Trouvelot et al 2014). …”
Section: Biocontrol and Other Agricultural Applicationsmentioning
confidence: 99%
“…Firstly, various studies indicated that WSC content of cold-tolerant cultivars were higher than in less tolerant cultivars [18]. Secondly, WSC not only supply energy required for plant defense, but also serve as signals for the regulation of defense genes [1921]. Overall, WSC are involved in a complex communication system necessary for coordination of metabolism with growth, development, and response to environmental changes and stress [2223].…”
Section: Introductionmentioning
confidence: 99%